Toward Highly Sensitive Polymer Photodetectors by Molecular Engineering. (29th September 2015) - Zhang, Luozheng; Yang, Tingbin; Shen, Liang; Fang, Yanjun; Dang, Li; Zhou, Nanjia; Guo, Xugang; Hong, Ziruo; Yang, Yang; Wu, Hongbin; Huang, Jinsong; Liang, Yongye
Abstract : Modified 3, 4‐ethylenedioxythiophene is employed as the conjugated side chain in conjugated polymers, which can significantly depress the dark current of the polymer photodetectors with little associated decrease in photovoltaic properties, thus enhanceing the detectivities. This approach can be applied to a variety of conjugated polymers covering a photoresponse range from UV to NIR.